Scully's medical problems in dentistry - Scully, Crispian (Edinburgh : Churchill Livingstone/Elsevier, 2014)
Suitable for students learning for the first time or practitioners needing to keep up-to-date with their knowledge, this title offers an account of general medical and surgical conditions as they apply to the practice of dentistry and oral healthcare
SECTION A: GENERAL SECTION B: ORGAN SYSTEMS MEDICINE SECTION C: OTHER SYSTEMS MEDICINE SECTION D: OTHER HEALTH ISSUES SECTION E: APPENDIX
Rev. ed. of Medical problems in dentistry / Crispian Scully. 6th ed. 2010.
Includes bibliographical references and index.
Keywords: Medicine; Dental Care; Oral manifestations of general diseases; Sick -- Dental care